KAJIAN PANJANG WORK ZONE DAN SISTEM PENGATURAN LALU LINTAS PADA PROYEK PERBAIKAN JALAN SEMARANG – GODONG - Ericha Marthina; Arini Novita Sari; Bambang Riyanto; Amelia Kusuma Indriastuti (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Road of Semarang – Godong is a type of road 2/2 UD currently under repair and greatly affected the result of the open – closed system, so the road was made the object of research. The aim of the research was to analyze the characteristics of the traffic, looking for the relationship between the volume of arrivals – long queues – the length of the work zone and reviewing traffic management system in the work zone. Analyze that done are analyze on existing condition and traffic management system with a length of 1,070 km using the method of the approach to the junction signal with two phases on MKJI 1997. This analysis also simulated on the variant length of the work zone. The results showed an analysis of existing conditions with observations data each cycle can’t proceed, so analysis only use data classification. The system settings can minimize the length of the traffic queues and the degree of saturation. From the results of the simulation of different length work zone obtained a value of DS and the minimum of the queue length 0.2 km. Other results obtained is increasingly large flows of arrival on-site queue getting longer, but the rate of increase in the existing conditions in the queue is larger compared to the results of the analysis of the traffic management system. Further research is required related factors on damage to roads and the length of the segment that is most optimal. To streamline traffic settings can use APILL portable or using more appropriate implementation method.